Pemanfaatan Rosella Untuk Sendi Yang Lebih Sehat - Gerardin Ranind Kirana; Reny Nugraheni; Vivien Dwi Purnamasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Lifestyle changes that occur in society to unhealthy lifestyles are the driving force for the emergence of various diseases that can affect the body's metabolism, one of which is gout. The aim of this community service activity is to increase the knowledge of the people of RT 02 RW 05 Kelurahan Banjarmlati Kecamatan Mojoroto Kota Kediri regarding the use of rosella plants to prevent gout. The method used is direct lecture and practical methods. The pre-test and post-test are carried out in the form of 5 true or false statements. The statements in the pre-test and post-test are adjusted to the material presented, namely the meaning of uric acid, limits for purine consumption, normal levels of uric acid, and prevention that can be done. The results of this activity showed that there was an increase in community knowledge, namely that from a total of 21 residents, the average number of people who answered correctly was 74.44% in the pre-test, and increased to 90.46% in the post-test. This community service activity is carried out by utilizing plants that residents can find around where they live as an alternative to preventing gout, so for the community this activity is very effective for them to do every day.